Sociological Approach on Trusting Transactions in Business to Al-Kafalah, Al-Hiwalah, Al-Rahn - Imam Muttaqin, Faruqi; Arifin, Tajul; Abdal (Yayasan Mentari Madani, 2023)
This journal presents the complex relationship between social factors and trust transactions in Islam-based businesses, focusing on Al-Kafalah, Al-Hiwalah, and Al-Rahn. The research findings reveal that social norms, community values, and religious principles play a key role in shaping ethical and sustainable business practices. The sociological implications of the research emphasize the importance of strengthening social values, applying religious principles, and promoting economic inclusion. Practical recommendations offer guidance for entrepreneurs and policymakers to develop business practices that are more inclusive and in line with Islamic principles. Thus, this abstract summarizes the contribution of this journal in providing an in-depth and practical understanding of the dynamics of Islam-based businesses from a sociological perspective